Is Creaky Voice a Valley Girl Feature? Stancetaking & Evolution of a Linguistic Stereotype - Pierre Habasque (Anglophonia)
The ‘Valley Girl’ stereotype came to be known in 1982 thanks to Frank & Moon Zappa’s eponymous hit song, which associated a wide variety of linguistic markers with the persona of a white, privileged, vapid, female adolescent. This ideological association has contributed to stancetaking in that using linguistic markers associated with Valspeak, the dialect supposedly spoken by Valley Girls, may alter the perception an outside observer has of the speaker. This linguistic stereotype evolved over time though, and new markers that were not originally part of Valspeak eventually became associated with this dialect. The aim of this paper is to explore the extent to which creaky voice has come to be associated with Valley Girls. It is argued that the birth of this stereotype tied the persona to specific linguistic markers, and that the integration of creaky voice to the dialect is evidence of an evolution of the stereotype. In order to test this hypothesis, a study on the perception of Valspeak was conducted in March/April 2019 on the campus of California State University, Northridge. 123 students participated in a quantitative study, and 70 other students participated in qualitative interviews. Results suggest that participants associate creaky voice with the Valley Girl persona. Creak can unsurprisingly be indexical of rather negative Valley Girl traits, such as shallowness, or stupidity, but other students associate it with characteristics that are not overtly socially stigmatized, such as economic privilege.